Interview of Julian P. Gudmundson by Brian Shoemaker - Gudmundson, Julian P. (Byrd Polar Research Center Archival Program, 2006)
Dorothy Bunning, pp.1 Dick Chappel, pp. 6, 9-10, 15, 43 ________ Rostagorev, pp. 6 Admiral Richard Byrd, pp. 10-11 ________Zoller, pp. 13 General Griswold, pp. 14 Gilbert Gilsner, pp. 14 Paul Dalrymple, pp. 15 Lowell Thomas, pp. 25 Admiral Reedy, pp. 25, 38 Martin Pomerantz, pp. 27 Mary Alice McWhinnie, pp. 34 Captain Howe, pp. 35, 44 Paul Berkheimer, pp. 35 President Lyndon B. Johnson, pp. 36 Lady Bird Johnson, pp. 37 Admiral Dufek, pp. 38 Admiral Tyree, pp. 38 Larry Gould, pp. 39 Paul Siple, pp. 40 Eddie Goodale, pp. 41 Dr. Jim Zumberge, pp. 32 The media can be accessed here: http://streaming.osu.edu/knowledgebank/byrd/oral_history/Julian_Gudmundson.mp3 Mr. Gudmundson was born in 1916 on a farm in Minnesota. After graduating from high school, he did not pass the physical exam for the Navy because of color blindness. He worked with a construction company building Army bases before joining a carpenter shop at Douglas Aircraft. In 1943, the Navy asked for volunteers for the Navy CB (Construction Battalion). After returning from Guadal Canal in 1945, Gudmundson returned to construction. In 1951, the Navy asked him to rejoin the Seabees for a project in Cuba. On return to the US he was assigned to a Naval Beach Group School in Virginia as an instructor. Gudmundson volunteered for Operation Deepfreeze and failed the color blindness test again, but “qualified” for construction. After construction training in Thule, he was sent to Antarctica. After unloading cargo from a ship at Little America, the men built a camp and moved cargo all winter. Upon return from Antarctica, Gudmundson was a recruiter. In 1961, he returned to Antarctica as a “blaster” for the construction of the nuclear power plant at McMurdo Sound. He describes the living conditions that he experienced. Gudmundson summarizes his experience with Admiral Byrd. He (Gudmundson) supervised the construction of Byrd Chapel in Antarctica and goes on to describe various experiences in Antarctica, including the presence of women. The high point of his 30 year ...